In vitro analysis of overall particulate contamination exposure during multidrug IV therapy: Impact of infusion sets. Issue 6 (8th March 2015) - Perez, Maxime; Décaudin, Bertrand; Abou Chahla, Wadih; Nelken, Brigitte; Barthélémy, Christine; Lebuffe, Gilles; Odou, Pascal
<x xml:space="preserve">Abstract</x> Background Drug incompatibilities, recognizable through precipitate, may have clinical consequences for patients, especially during multidrug IV therapies, where vancomycin and piperacillin are present. Drug concentration and infusion set influence the overall particulate contamination of pediatric infusion protocols. The use of multi‐lumen infusion sets could prevent such incompatibilities. Our goal was to define and assess a new way to infuse these drugs during leukemia treatment in children. Procedures This in vitro study focused on a pediatric multidrug protocol for patients diagnosed with lymphoblastic leukemia and receiving allogeneic transplantation. Different vancomycin concentrations were tested to infuse incompatible drugs simultaneously without any particle formation (optimized multidrug protocol). A dynamic particle count test was used over 24 hr to evaluate the overall particulate contamination of our standard and optimized multidrug protocols, using both a standard and a multi‐lumen infusion set. Results No visible particles were detected on a decreased vancomycin concentration compared to the standard dose. For the optimized multidrug protocol, the use of a multi‐lumen infusion set reduced overall particulate contamination by 68%, compared to the standard infusion set (P = 0.002). Large‐sized particles were significantly reduced when using the multi‐lumen infusion set approximately 60% (P = 0.027) and 90% (P = 0.009) for particle sizes ≥10 μm and 25 μm, respectively. Conclusions This study demonstrates that a large number of particles can be administered during parenteral multidrug infusion. The choice of drug concentration and/or the type of infusion set may reduce this. Further studies are required to evaluate adverse clinical effects. Pediatr Blood Cancer 2015;62:1042–1047. © 2015 Wiley Periodicals, Inc.